2014
DOI: 10.1128/cmr.00062-13
|View full text |Cite
|
Sign up to set email alerts
|

Host Immune Status and Response to Hepatitis E Virus Infection

Abstract: SUMMARY Hepatitis E virus (HEV), identified over 30 years ago, remains a serious threat to life, health, and productivity in developing countries where access to clean water is limited. Recognition that HEV also circulates as a zoonotic and food-borne pathogen in developed countries is more recent. Even without treatment, most cases of HEV-related acute viral hepatitis (with or without jaundice) resolve within 1 to 2 months. However, HEV sometimes leads to acute liver failure, chronic infection, or e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
119
0
11

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 138 publications
(135 citation statements)
references
References 348 publications
(449 reference statements)
5
119
0
11
Order By: Relevance
“…Indeed, only a limited number of cases of transfusion-transmitted HEV have been reported despite administration of contaminated blood products (3,7,30,31). In addition, a recent retrospective survey of United Kingdom's plasma pool surprisingly showed that only one-half of HEV viremic Brit- HEV RNA-containing inocula derived from EDTA plasma (patients HEV0014 and HEV0122; n ϭ 4, respectively), a cryopreserved liver biopsy specimen (patient HEV0122; n ϭ 2), feces (patient HEV0069; n ϭ 2), or P7 culture supernatant of patient HEV0069 feces (n ϭ 7) (see Materials and Methods).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, only a limited number of cases of transfusion-transmitted HEV have been reported despite administration of contaminated blood products (3,7,30,31). In addition, a recent retrospective survey of United Kingdom's plasma pool surprisingly showed that only one-half of HEV viremic Brit- HEV RNA-containing inocula derived from EDTA plasma (patients HEV0014 and HEV0122; n ϭ 4, respectively), a cryopreserved liver biopsy specimen (patient HEV0122; n ϭ 2), feces (patient HEV0069; n ϭ 2), or P7 culture supernatant of patient HEV0069 feces (n ϭ 7) (see Materials and Methods).…”
Section: Discussionmentioning
confidence: 99%
“…In immunocompetent individuals, HEV infection is mainly self-limiting and often asymptomatic and thus remains largely underdiagnosed. HEV infections in immunosuppressed patients, such as solid-organ transplant recipients, often persist and can progress quickly to liver fibrosis and cirrhosis (2)(3)(4).…”
mentioning
confidence: 99%
“…Patients with underlying liver disease and patients who are immunosuppressed or immunocompromised are at particular risk. 2 HEV is a non-enveloped, single-stranded, positive-sense RNA virus. It is the only member of the genus Hepevirus in the family Hepeviridae.…”
Section: Introductionmentioning
confidence: 99%
“…5,6 7 The largest randomized, controlled phase III vaccine trials to date using this recombinant vaccine was conducted in Jiangsu Province, China, and enrolled 112,604 healthy adult participants. [8][9][10] A vaccine efficacy of approximately 79.2% (95% confidence interval [CI], 67.7% to 86.6%) in the prevention of infection was demonstrated with greater protection rate against clinical illness. 10,11 Another HEV vaccine based on recombinant HEV viral capsid protein was also tested clinically, demonstrating high efficacy against HEV infection and disease.…”
Section: Introductionmentioning
confidence: 99%
“…[8][9][10] A vaccine efficacy of approximately 79.2% (95% confidence interval [CI], 67.7% to 86.6%) in the prevention of infection was demonstrated with greater protection rate against clinical illness. 10,11 Another HEV vaccine based on recombinant HEV viral capsid protein was also tested clinically, demonstrating high efficacy against HEV infection and disease. 12, 13 14 The above-mentioned Hecolin Ò contains aluminum-based adjuvants for enhancing the antigen immunogenicity.…”
Section: Introductionmentioning
confidence: 99%